Fatality as a Feature of Medical Care - Ruiz-Sada Pablo (Romanian Journal of Internal Medicine, 2016)
Taking advantage of an interesting clinical scenario, we want to introduce a discussion about fatality in our daily practice and the need to accept that. An 80 year-old man with non-traumatic spontaneous bleeding tendency came to the clinics. Although being on warfarin as a consequence of primary thrombotic prophylaxis due to an atrial fibrillation, full assessment was performed. Not only the rare entity found on him, but also the severe complication that happened afterwards challenged clinicians and led them to risky treatment options.